Psychoanalysis and suggestion therapy : their technique, applications, results, limits, dangers and excesses - Stekel, Wilhelm, 1868-1940 (International library of psychology, 1999)
First Published in 1999. Routledge is an imprint of Taylor & Francis, an informa company.